Some Dynamic Inequalities of Hilbert’s Type - A. M. Ahmed; Ghada AlNemer; M. Zakarya; H. M. Rezk (Journal of Function Spaces)
This paper is concerned with deriving some new dynamic Hilbert-type inequalities on time scales. The basic idea in proving the results is using some algebraic inequalities, Hölder’s inequality and Jensen’s inequality, on time scales. As a special case of our results, we will obtain some integrals and their corresponding discrete inequalities of Hilbert’s type.